РОЗРАХУНОК ВОЛЬТ-АМПЕРНОЇ ХАРАКТЕРИСТИКИ ШУНТУВАЛЬНОГО РЕАКТОРА З ПРОМІЖКАМИ В СТРИЖНІ - Іванков, В.Ф.; Басова, А.В.; Шульга, Н.В. (Інститут електродинаміки НАН України, Київ, 2015)
Determination of volt-ampere characteristic of the reactor is presented at magnetic system calculation, both by analytical method and based on numerical finite-element analysis with application ANSYS software. The example of calculation and measurement is provided for single-phase reactor rated for power 80 МVАr, 765 kV. References 5, figures 8.